Improving Students’ Speaking ability Through Alley Debates Strategy - Afore Tahir Harefa; Roi Jefri Ndruru (PT. Marosk Zada Cemerlang, 2022)
The syllabus of curriculum 2013 (K-13) of SMA implied that speaking categorized as a skill. Based on researcher’s observation and interview with the English at the eleventh grade of SMA N 1 Ulunoyo the researcher found some problems dealt with this language skill, namely the students are unable to compose some expressions in giving opinion, the students are not able to pronounce the words provide opinions and thought, and the students are lack of vocabularies. Therefore, the purpose of this research is to overcome those problems. The researcher has applied Classroom Action Research (CAR) to measure the Alley Debates Strategy impact at the eleventh grade of SMA Negeri 1 Ulunoyo. The researcher has conducted two cycles and every cycle was in 2 meetings. Average of students’ score in cycle I is 56.25, the lowest mark is 50 and the highest mark is 75. Thus, most of the students’ do not achieve the MCC that have been decided with score 75, and continued to conduct next cycles. The averages of the students’ score in cycle II was 79. The lowest mark in Cycle II is 75 and the highest mark is 90. Thus, the students achieve the MMC decided, the researcher has found the students’ ability increased. Finally, the researcher suggested to the English teachers to apply this strategy in teaching speaking skill. It is able to encourage the students to speak encourage, and engaged the students high motivation during the teaching and learning process.